Melampaui Keterampilan Teknis: Analisis Kesenjangan Antara Harapan Petani dan Realitas Kinerja Penyuluhan Pertanian - Rizki Nandi; Hendry Kurniawan; Heffi Christya Rahayu (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the level of rice farmer satisfaction with the performance of agricultural extension services in Pasir Baru Village, Rokan Hulu Regency. This research specifically aimed to identify the priority attributes of the extension service that require improvement and to measure the overall satisfaction level of the farmers. Materials and methods. This research employed a descriptive quantitative approach. The study involved a census of 45 rice farmers in Pasir Baru Village. Data were collected through questionnaires measuring the perceived importance and performance levels of 21 service attributes. The collected data were then analyzed using the Customer Satisfaction Index (CSI) to determine the overall satisfaction level and Importance-Performance Analysis (IPA) to identify strategic priorities for service improvement. Results. The analysis revealed that the overall farmer satisfaction index (CSI) was 74.504%, classifying the farmers' satisfaction level as "Satisfied". The Importance-Performance Analysis (IPA) indicated that the main priority for improvement (Quadrant I) was the "provision of agricultural facilities and infrastructure." Meanwhile, several other attributes, such as the extension officers' competence in direct field practice, friendliness, and responsiveness, were in Quadrant II, indicating high performance that should be maintained. Conclusions. The study concludes that while farmers are generally satisfied with the extension services, there is a critical need for improvement in the provision of facilities and infrastructure, which is the top priority. Improving this specific aspect is crucial to elevate the overall satisfaction from "Satisfied" to a higher level and to enhance the effectiveness of the agricultural extension program in the region.